(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2014)
Rezults the progress of long-term monitoring (1974–2013) model population of Homogyne alpina (L.) Cass. (Asteraceae), during demutation change in subalpine meadows in the Carpathians are summarized. Main features of structural transformations and principles of self-regulation in this population were revealed. It was concluded that micropopulations have special role as centers of flow formation generation and conservation of heterogeneity of population elements.